2021
DOI: 10.1111/bjh.17368
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of regulatory T cells on glucocorticoid sensitivity in patients with immune thrombocytopenia: a multicentre, prospective clinical study

Abstract: Glucocorticoids (GC) are used as the first-line treatment of immune thrombocytopenia (ITP), but 10-20% of patients are insensitive to them. Regulatory T cells (Tregs) can maintain immune tolerance in autoimmune diseases. The present research pooled 55 patients with newly diagnosed ITP and 44 healthy volunteers from seven hospitals. All patients received GC treatment and were divided into GC-sensitive and GC-insensitive groups according to the curative effect after 2 weeks of treatment. The levels of lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Another study demonstrated that higher proportions of CD56 + or CD2 + lymphocytes were predictors for poor response to corticosteroid, and selected the cut‐off value of CD56 + lymphocytes at 24.5% as well as CD2 + lymphocytes at 85.7% 22 . In addition, Li et al found that higher level of CD8 + CD25 str+ regulatory T‐cell subgroup (Treg, cut‐off value set at 0.09%) could identify patients with sensitivity to corticosteroid 23 . Nevertheless, none of the above studies have investigated the predictors for long‐term responses or relapse, and measurement of these factors in clinical practice is not easy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that higher proportions of CD56 + or CD2 + lymphocytes were predictors for poor response to corticosteroid, and selected the cut‐off value of CD56 + lymphocytes at 24.5% as well as CD2 + lymphocytes at 85.7% 22 . In addition, Li et al found that higher level of CD8 + CD25 str+ regulatory T‐cell subgroup (Treg, cut‐off value set at 0.09%) could identify patients with sensitivity to corticosteroid 23 . Nevertheless, none of the above studies have investigated the predictors for long‐term responses or relapse, and measurement of these factors in clinical practice is not easy.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, Li et al found that higher level of CD8 + CD25 str+ regulatory T-cell subgroup (Treg, cut-off value set at 0.09%) could identify patients with sensitivity to corticosteroid. 23 Nevertheless, none of the above studies have investigated the predictors for long-term responses or relapse, and measurement of these factors in clinical practice is not easy. In contrast to that, BMI is an easily obtained index in clinical practice.…”
Section: F I G U R Ementioning
confidence: 99%
“…CD8+ Tregs yield the ability to activate autoreactive T cells, cause proliferation of autoreactive T cells and inhibit the release of pro-inflammatory cytokines through expression of high levels of FoxP3, as well as GC induced tumor necrosis factor (TNF) receptor, TNF receptor type 2 and CTLA-4 [ 56 ]. A recent study in newly diagnosed adult ITP patients ( n = 55), who did not receive treatment in at least 3 months prior to enrollment, demonstrated that in the GC-sensitive group the levels of CD8+ CD25str+ Tregs were significantly higher than in the GC-insensitive group, while no obvious changes were observed for CD4+ Tregs [ 57 ]. This suggested that CD8+ Tregs cells may possibly be predictive for GC sensitivity [ 57 ], however, further validation is warranted.…”
Section: T Cell Homeostasismentioning
confidence: 99%
“…A recent study in newly diagnosed adult ITP patients ( n = 55), who did not receive treatment in at least 3 months prior to enrollment, demonstrated that in the GC-sensitive group the levels of CD8+ CD25str+ Tregs were significantly higher than in the GC-insensitive group, while no obvious changes were observed for CD4+ Tregs [ 57 ]. This suggested that CD8+ Tregs cells may possibly be predictive for GC sensitivity [ 57 ], however, further validation is warranted. Furthermore, differentially skewed CD4+/CD8+ ratio combined with a higher absolute number of CD19+ B lymphocytes has been observed in newly diagnosed adult ITP patients that responded to monotherapy with corticosteroids or corticosteroids in combination with IVIg compared to the non-responder group [ 51 ].…”
Section: T Cell Homeostasismentioning
confidence: 99%
“…In the literature up to 20% of patients do not respond sufficiently. The blood levels of CD8+ CD25+ regulatory T‑cells (activated Tregs) in steroid responsive cases are described as being significantly higher, giving predictive information in sensitivity to corticosteroid treatment if examined [ 7 ].…”
mentioning
confidence: 99%